Clinical Manifestations of Mucous Membrane Pemphigoid in a Tertiary Center - Mameletzi, E.; Hamedani, M.; Majo, F.; Guex-Crosier, Y. (Klinische Monatsblätter für Augenheilkunde, 2012)
Mucous membrane pemphigoid (MMP) is a progressive inflammatory disease of autoimmune etiology. We performed a retrospective analysis of clinical signs and treatment on 16 patients. Conjunctival biopsies were performed in all patients and showed typical immuno-deposits at the basement membrane zone. The mean age at presentation was 69 years, 60 % were female.12 patients demonstrated ocular involvement (11 bilaterally). At the time of referral to our hospital, 92 % had reached an advanced stage III or IV. All patients presented conjunctival fibrosis with resultant fornix foreshortening. Trichiasis and symblepharon were found in 11 patients. Keratitis was found in 11 patients resulting in ulceration in 5 cases. Complications required surgical interventions included: entropion surgery (n = 2), tarsorrhaphy (n = 1), amniotic membrane transplantation (n = 2), keratoplasty (n = 1). Systemic immunomodulatory therapy is the treatment of choice. Dapsone (n = 8), steroids (n = 8), azathioprine (n = 5), cyclophosphamide (n = 2), mycophenolate mofetil (n = 4) and methotrexate (n = 1) were used concomitantly or consecutively. Early diagnosis can prevent ocular complications. Immunomodulatory therapy has provided an avenue for preserving vision. The management of MMP requires a multidisciplinary approach.
Keywords: MMP; mucous membrane pemphigoid; entropion; symblepharon; dapsone